Representasi Konsep Diri (Self Concept) dalam Lirik Lagu “Mengenal Lebih Jauh” Karya Nuca : Analisis Semiotik Ferdinand De Saussure - Aisyah Salwa Salsabila (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Music and song lyrics serve as a means of self-expression capable of conveying messages, feelings, and representing a person's self-concept in the face of reality and social expectations. This research focuses on a semiotic analysis of the lyrics of the song